PEMETAAN JALUR “PAKET WISATA PEDESAAN” DI DESA WISATA PENGLIPURAN, KECAMATAN BANGLI, KABUPATEN BANGLI - I G. A. O. Mahagangga; I. B. Suryawan; S. Nugroho; I P. Sudana (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2016)
The potential of such unique nature and culture in the village Penglipuran it is proper to be developed and introduced to the tourists so that rural communities receive economic benefits, such as the availability of additional jobs and increase income by providing services as a local tour guide, provision culinary, providing soulvenir typical village Penglipuran and receiving income in the form of receipts village onggos admission and parking. Businesses that can be taken is the form of making the tour packages of innovative rural to attract the number of tourists visiting the village Penglipuran and improving the quality of human resources supporting. To develop further Penglipuran village, Pengabdi team has managed to make the packaging countryside tour package entitled